Determination of civil engineering construction time duration - Chong, C.T (University Malaysia Sarawak, (UNIMAS), 2006)
This research will analyze and compare the theoretical methods applied in case studies, drawing out their differences and similarities. This research also seeks to draw out the problem encountered of each case study in estimating time. This research will also looks into the suitability and effectiveness of each method in determining projects' duration.